2015
DOI: 10.1111/mmi.13257
|View full text |Cite
|
Sign up to set email alerts
|

Increased cytoplasm viscosity hampers aggregate polar segregation in Escherichia coli

Abstract: SummaryIn Escherichia coli, under optimal conditions, protein aggregates associated with cellular aging are excluded from midcell by the nucleoid. We study the functionality of this process under sub-optimal temperatures from population and time lapse images of individual cells and aggregates and nucleoids within. We show that, as temperature decreases, aggregates become homogeneously distributed and uncorrelated with nucleoid size and location. We present evidence that this is due to increased cytoplasm visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 54 publications
(118 reference statements)
5
20
0
Order By: Relevance
“…Previously, E . coli strains expressing an IbpA-YFP fusion protein have been used to microscopically visualize intracellular PAs, which appeared as punctate and polarly located fluorescent foci inside the cytoplasm of healthy, living cells [ 10 , 15 , 33 ]. However, given the potential of many commonly used fluorescent proteins to cause label-induced oligomerization and trivial foci formation, this IbpA-YFP reporter has been suggested to yield a biased view on intracellular PA dynamics [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, E . coli strains expressing an IbpA-YFP fusion protein have been used to microscopically visualize intracellular PAs, which appeared as punctate and polarly located fluorescent foci inside the cytoplasm of healthy, living cells [ 10 , 15 , 33 ]. However, given the potential of many commonly used fluorescent proteins to cause label-induced oligomerization and trivial foci formation, this IbpA-YFP reporter has been suggested to yield a biased view on intracellular PA dynamics [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular PA movement serves as a proxy for the metabolic status of the cell Although intracellular PA (re)assembly and movement was initially thought to be strictly diffusion-based and thus energy-independent (Winkler et al, 2010;Coquel et al, 2013), more-detailed insights into the physical nature of the bacterial cytoplasm and its glass-like properties have indicated that the mobility of such larger intracellular structures is progressively constrained with increasing size, and that cellular metabolism is required to fluidize the cytoplasm, in order to allow these structures to escape their local environment and explore larger regions of the cytoplasm (Parry et al, 2014). Recently, polar segregation of PAs has been shown to be hampered in conditions of increased cytoplasmic viscosity (Oliveira et al, 2016), indicating the latter, modulated by factors such as metabolic activity, temperature and osmolality (Weber et al, 2012;Parry et al, 2014;Oliveira et al, 2016), can indeed affect PA behavior. In order to fully examine the impact of these metabolism-dependent glass-like dynamics of the bacterial cytoplasm on PAs, we monitored live E. coli MG1655 ibpAyfp cells, in which PAs are fluorescently traceable (Lindner et al, 2008), in different environments and quantified their macromolecular motion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are claims that transport of aggregates to the poles is energy-driven as studies on reassembly of pressure dissociated IBs revealed that confinement to the pole is caused by the presence of the nucleoid but reassembly of smaller aggregates into large IBs does not occur in energy and nutrient depleted cells [16]. However, there are also reports stating that exclusion of aggregates from mid-cell to the pole is energy-free, and simply results from nucleoid exclusion [17,20,[28][29][30]. Restriction of aggregates to the pole was also observed during treatment with substances disrupting the protein motive force, suggesting an energy independent process of aggregation [20].…”
Section: Cellular Formation Of Ibsmentioning
confidence: 98%
“…There is still controversy whether IB formation is a passive process only depending on physically interacting protein chains or if it is an energy-driven process that requires active involvement of the cell [15][16][17].…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%